Effect of statins on atrial fibrillation: collaborative meta-analysis of published and unpublished evidence from randomised controlled trials. - Rahimi, K; Emberson, J; McGale, P; Majoni, W; Merhi, A; Asselbergs, F; Krane, V; Macfarlane, P; PROSPER Executive (2011)
To examine whether statins can reduce the risk of atrial fibrillation.